2021
DOI: 10.24349/acarologia/20214413
|View full text |Cite
|
Sign up to set email alerts
|

Communities of predatory mites (Phytoseiidae and Stigmaeidae) in different environments of the Brazilian Pampa

Abstract: The Brazilian Pampa presents a high diversity of fauna and flora within a mosaic of environments. The aim of this study was to evaluate the assemblages of predatory mites (Phytoseiidae and Stigmaeidae) in three different Pampa environments: Grassland shrub vegetation, Grazing Exclusions fenced for six years and Riparian Forest with tree vegetation. Phytoseiidae and Stigmaeidae were evaluated with a total of 324 plant sampled from nine sites in three environments. Twenty-two Phytoseiidae species and six Stigmae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies on mite diversity are needed to monitor areas that can serve as reservoirs for natural enemies. It is important to assess how predators remain in ecosystems and evolve over time, in addition to understanding the potential of these species in biological control (Toldi et al 2021). The aims of this study are to know the diversity of phytoseiids found in grape-producing regions located in northern Portugal, in the sub-regions of the Ave, Cávado, Douro, Lima and Minho Rivers and compare phytoseiids abundance and richness in the evaluated regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on mite diversity are needed to monitor areas that can serve as reservoirs for natural enemies. It is important to assess how predators remain in ecosystems and evolve over time, in addition to understanding the potential of these species in biological control (Toldi et al 2021). The aims of this study are to know the diversity of phytoseiids found in grape-producing regions located in northern Portugal, in the sub-regions of the Ave, Cávado, Douro, Lima and Minho Rivers and compare phytoseiids abundance and richness in the evaluated regions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on mite diversity are needed to monitor areas that can serve as reservoirs for natural enemies. It is important to assess how predators remain in ecosystems and evolve over time, in addition to understanding the potential of these species in biological control (Toldi et al . 2021).…”
Section: Introductionmentioning
confidence: 99%